2024
DOI: 10.3390/electronics13081552
|View full text |Cite
|
Sign up to set email alerts
|

Design of Multi-Band Bandstop Filters Based on Mixed Electric and Magnetic Coupling Resonators

Jie Luo,
Jinhao Zhang,
Shanshan Gao

Abstract: In this paper, multi-band bandstop filters (BSFs) based on mixed electric and magnetic coupling resonators are proposed. These proposed structures include a multimode resonator based on symmetrical open-circuit branches, including upper- and lower-branch filter circuits. Through this design, the center frequencies of the stopbands can be flexibly and autonomously adjusted. In addition, the filters proposed in this paper have excellent characteristics, such as miniature dimensions and abrupt roll-off skirts. Fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 20 publications
(39 reference statements)
0
2
0
Order By: Relevance
“…The bottom reflective layer consists of a gold film with m = 2 μm, which is much greater than the skinning depth of 0.06 μm for gold, and ensures that the terahertz wave is completely absorbed. 27,28 The intermediate dielectric layer is a SiO 2 layer with a dielectric permittivity of 2.13. The top layer is a VO 2 patterned layer with the structure shown in Fig.…”
Section: Structure Design and Numerical Modelmentioning
confidence: 99%
“…The bottom reflective layer consists of a gold film with m = 2 μm, which is much greater than the skinning depth of 0.06 μm for gold, and ensures that the terahertz wave is completely absorbed. 27,28 The intermediate dielectric layer is a SiO 2 layer with a dielectric permittivity of 2.13. The top layer is a VO 2 patterned layer with the structure shown in Fig.…”
Section: Structure Design and Numerical Modelmentioning
confidence: 99%
“…In order to make up for these shortcomings, people started with the material of absorbers [16] and found that nanoarray-placed precious metals have high optical absorption and excellent electrical conductivity [17][18][19], which is good for solving the problem of the low absorption rate of solar absorbers, but considering limited resources as well as the cost [20,21], it has not been put into practical use in a large number of cases. Many metamaterials have also been studied to achieve perfect performance with the use of artificially orientated synthetic materials, but the achieved performance is limited [22][23][24][25]. Considering the limitations of heavy metals and metamaterials, we choose Ti and its oxide TiO 2 , which is a potential high-temperature material with a unique energy gap structure that enhances the absorption of photons by the material, which is helpful in extending the bandwidth [26].…”
Section: Introductionmentioning
confidence: 99%